Regulatory Pathway for Registration of Biosimilars in Russia - Shekhar, Raj; Hallur, Namrata; Muralidharan, P; Puranik, S B (Asian Journal of Pharmaceutical Research and Development, 2020)
Biological products or biopharmaceuticals are medicinal products derived from living organism systems and manufactured by using modern biotechnology that differ widely from the conventional synthetic drugs. According to some estimates, Russia is poised to be among the top five global pharmaceutical Markets in terms of value in the next couple of years. Due to the impetus shown by the government regarding the evolution of the Russian regulatory framework for pharmaceutical products, this and other market trends suggest that Russia will soon become a powerhouse destination for pharmaceutical manufacturers and contract research organizations. Russian law allows the registration of biological drugs defined as medicinal products containing a biological active substance. A biological active substance is a substance that is produced by or extracted from a biological source and requires physical, chemical and biological testing, characterization of its quality, along with its production process and control. It does not define a biosimilar, nor it provides a regulatory framework for the biosimilar approval; this implies that a full clinical developmental program, similar to the innovator biological product, must be completed even for a biosimilar. An applicant must submit a registration dossier to the Ministry of Health (MoH), the regulatory body for drugs evaluation, with its affiliation Federal State Budgetary Institution - Scientific Centre for Expert Evaluation of Medicinal Products (FSBI-SCEMP). The complete dossier in Russian must be submitted to the MoH, and should include administrative documents, description of pharmaceutical properties and data about the manufacturing process, quality control, preclinical studies (pharmacological and toxicological) and clinical studies regarding the biological drug. Russia follows the European Guidelines for biosimilars for data requirements for the registration of a biological drug. Today, Russia stands on the verge of becoming a major force in the global pharmaceutical market. The exact contours of its future are as yet undefined; challenges and opportunities co-exist in equal measure. The Russia of today is not the Russia of yesteryears, and tomorrow’s Russia will take yet a different face again. The objective of this manuscript is to explore the Regulatory pathway for registration of Biosimilars in Russia.